Ascorbic Acid and/or 24-Epibrassinolide Trigger Physiological and Biochemical Responses for the Salt Stress Mitigation in Potato (Solanum tuberosum L.) - Upadhyaya, Chandrama Prakash; Bagri, Deepak Singh; Upadhyay, Devanshi Chandel (International Journal of Applied Sciences and Biotechnology, 2015)
In the present study, we examined the role of ascorbic acid (AsA, vitamin C) and/or 24-epibrassinolide (EBL, an active BR) in mitigation of salt-induced stress in potato (Solanum tuberousum L). The 10-d-old plants were exposed to 150 mM NaCl and they were subsequently treated by ASA and/or EBL. The salt stress reduced significantly the plant growth, tuber yield, total chlorophyll and increased proline content and electrolyte leakage in the leaves. Toxic effects induced by salt stress were completely overcome by the combined exogenous application of AsA and EBL. The AsA and/or EBL treatments improved the growth parameters of the salt treated plants, such as shoot length, tuber number and size, fresh and dry mass and other physiological parameters. Our data also indicated that applications of AsA and EBL up-regulated the stress regulating plant hormone such as IAA, IBA and activities of the antioxidant enzymes, such as catalase (CAT), peroxidase (POX), superoxide dismutase (SOD), ascorbate peroxidase (APX) and under salt stress. Int J Appl Sci Biotechnol, Vol 3(4): 655-667